Nilai Nilai Eksistensi Tradisi Sekaten Dalam Perspektif Hukum Adat Dan Hukum Islam - Farizki Alam; Salsabella Vanisa Putri; Grace Oktavia; Anggita Yuniar; Anida Ayu Aminati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research focuses on the values ​​of the existence of the sekaten tradition in the perspective of customary law and Islamic law, as stated in article 18B paragraph 2 which states that